The role of interfacial impedance on poroelastic reflection coefficient - Qi, Q.; Müller, T.; Gurevich, Boris (2015)
The characteristics of the seismic P-wave reflection coefficient can depend on the properties of the interface separating two dissimilar poroelastic half-spaces. This interface behavior can be characterized by an interfacial impedance which is associated with various petrophysical scenarios. We study the effects of the interfacial impedance on wave propagation across the interface between gas- and fluid-saturated media as well as a fluid/porous-medium contact. We obtain the reflection coefficient accounting for the interfacial impedance for all frequencies and angles by solving the corresponding boundary value problem. The interfacial impedance shows small influence on the P-wave reflection coefficient for the gas/water contact at seismic frequencies. However, it substantially changes the amplitude and phase angle of the reflected P-wave for a fluid/porous-medium contact.